Sym-bolon historii i mitu - Gajewska, Grażyna (Er(r)go. Teoria - Literatura - Kultura, 2003)
Grażyna Gajewska „Sym-bolon historii i mitu” [The Sym-bolon of history and myth] The article focuses on history and myth as two narrative forms of the representation of the past and explores differences between them.